PENINGKATAN SIFAT GLASS-CERAMICS FLY ASH TERVITRIFIKASI DENGAN PENAMBAHAN 30 WT.% ALUMINIUM SILIKAT DAN PENGATURAN SUHU SINTER - Nurzal, Nurzal; Pratiwi, Putri; Handra, Nofriady; Perdana, Mastariyanto; Hafni, Hafni (ITP Press, 2025)
This study investigates the effects of adding 30 wt.% aluminum silicate and varying sintering temperatures on the density and hardness of vitrified fly ash glass ceramics. Fly ash, a waste by product from coal combustion at the Suralaya thermal power plant has long posed environmental challenges. To mitigate these impacts, this research explores its utilization in producing glass ceramics. The samples were prepared as cylindrical samples with a diameter of 15 mm and thickness of 5 mm, and were fabricated using uniaxial pressing at 120 MPa. The samples were sintered at 1050, 1100, and 1150 °C with a heating rate of 5 °C/min. Experimental results reveal that adding 30 wt.% AS significantly improves the density from 2.31 to 2.51 g/cm³ and hardness from 443 to 2418.55 MPa compared to 100 wt.% fly ash. Optimal density and hardness were achieved at a sintering temperature of 1150 °C.